“Influencia de las fases lunares en el comportamiento morfológico en plantones de bolaina blanca (guazuma crinita mart.), en el vivero pucayacu IIAP-San Martín” - Ramírez Saavedra, Maricela (2015)
The light from the moon, according to the proper intensity of each phase involved or influence the germination and plant growth, because moles rays have the ability to penetrate through the soil, manifested through ascent or descent sap. This study aimed to evaluate the influence of the moon phases in the morphological behavior of seedlings of white Bolaina (Guazuma crinita Mart.) In nursery stage. The work was done in the forest nursery Pucayacu Research Center, llAP San Martin, in the village of Bello Horizonte. Design of randomized complete block (RCBD), which consists of 4 blocks, 4 treatments (lunar phases), with a total of 16 experimental units was used. lt was determined that the plant bolaina, have different morphological behavior according to the moon phase in which it was planted, resulting in sorne cases better heights and diameters, and greater weight of dry matter and quality, predicting their ability to survive in field . The study shows that treatment 4 (crescent), white bolaina plants had better morphological behavior, further Dickson quality index, these plants having greater chances of survival in the field. lt is recommended that this research having as repetitiva suggestion planted in each lunar phase for each month to see if these results hold or vary the planting season. Keywords: white Bolaina, moon phase, nursery, quality indices